2019
DOI: 10.3390/su11082192
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptive Emergency First Intelligent Scheduling Algorithm for Efficient Task Management and Scheduling in Hybrid of Hard Real-Time and Soft Real-Time Embedded IoT Systems

Abstract: Industrial revolution is advancing, and the augmented role of autonomous technology and embedded Internet of Things (IoT) systems is at its vanguard. In autonomous technology, real-time systems and real-time computing are of core importance. It is crucial for embedded IoT devices to respond in real-time; along with fulfilling all the constraints. Many combinations for existing approaches have been proposed with different trade-offs between the resources constraints and tasks dropping rate. Hence, it highlights… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…The main difference is that, if modern technologies such as edge computing and RT-IoT are considered in the design of EVs, they can help in offloading the system-on-chip ECUs. It has been suggested in these studies that it is quite possible to model an autonomous EV as an RT-IoT system [13,24]. It is envisioned that modern EVs are real-time IoT systems with the constraint of energy and battery.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…The main difference is that, if modern technologies such as edge computing and RT-IoT are considered in the design of EVs, they can help in offloading the system-on-chip ECUs. It has been suggested in these studies that it is quite possible to model an autonomous EV as an RT-IoT system [13,24]. It is envisioned that modern EVs are real-time IoT systems with the constraint of energy and battery.…”
Section: Related Workmentioning
confidence: 99%
“…Other scheduling algorithms include hierarchical scheduler [43,44,45] based on Scheduling Framework For Fast Prototyping (SF3P) [46] and is used to explore and prototype a hierarchical composition of the real-time scheduler. A younger algorithm for emergency first scenarios of complex tasks having different types was proposed by Malik et al [13] in IoT space and suggested that, if tasks are carefully modeled, it will never drop a hard-deadline task. The current position of the state-of-the-art is summarised in Table 1.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…This scheduling is the most significant component of processing in real-time systems in order to prioritize and perform the significant tasks within the deadline and also to manage all remaining tasks with low priority by proper allocation of these tasks during the idle time of the processor. Hence, this leads to proper utilization of the processor while increasing the performance during the necessary time [9].…”
Section: Real Time Systemmentioning
confidence: 99%